Guidance for research on the COVID-19 disease in times of pandemic - Oya KALAYCIOGLU (Journal of Health and Social Sciences)
This study is aimed at examining the manner of use of internet and phone surveys and making suggestions related to sample selection strategies during the COVID-19 outbreak. As the influence of the COVID-19 pandemic spreads worldwide, many researchers are engaged in telephone and internet surveys to assess the socioeconomic impacts of the outbreak of the disease and the emerging needs of societies during this pe- riod. However, the data collection methods requiring access to technology and the ability to use it may lead to under-representativeness of socioeconomically deprived groups. In emergency situations, although this can be a legitimate limitation, it should be reported by the researchers and optimal effort should be made to increase representativeness. In order to ensure that the population is adequately represented with a sample, the choice of survey mode and sampling strategy should be determined based on the research objectives, socio-demographic characteristics of the target population and the available resources. However, most sur- vey research being conducted during the outbreak of COVID-19 disease lack proper justification of the sampling strategy used and neglect to address the limitations due to under-represented communities. This may consequently result in misleading and overgeneralized findings. Therefore, guidance to researchers con- cerning appropriate survey methods and sample selection strategies that could be used in surveys during the COVID-19 pandemic are needed.The comparison of advantages and disadvantages of different survey stra- tegies presented in this study are expected to contribute to the methodological literature in data collection.